2022
DOI: 10.3389/fnbeh.2022.826831
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and Sociality: Aggression and Affiliation Shape Vole Social Relationships

Abstract: The formation of selective social relationships is not a requirement of group living; sociality can be supported by motivation for social interaction in the absence of preferences for specific individuals, and by tolerance in place of social motivation. For species that form selective social relationships, these can be maintained by preference for familiar partners, as well as by avoidance of or aggression toward individuals outside of the social bond. In this review, we explore the roles that aggression, moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 111 publications
1
5
0
Order By: Relevance
“…Touch can be aggressive (i.e., pain-causing), or socio-positive (referred to as touch in our paper). Aggressive touch, is linked to the establishment of a dominance hierarchy and is usually counterproductive in the formation of enduring bonds and continued maintenance of social bonds [68,69]. Socio-positive touch can have a reproductive, sexual or caring functions, and can vary in its duration [70].…”
Section: Glossarymentioning
confidence: 99%
“…Touch can be aggressive (i.e., pain-causing), or socio-positive (referred to as touch in our paper). Aggressive touch, is linked to the establishment of a dominance hierarchy and is usually counterproductive in the formation of enduring bonds and continued maintenance of social bonds [68,69]. Socio-positive touch can have a reproductive, sexual or caring functions, and can vary in its duration [70].…”
Section: Glossarymentioning
confidence: 99%
“…Several studies in humans have shown that peripheral administration of oxytocin is associated with increased in-group bias and that oxytocin may facilitate the emergence of intergroup conflict and violence ( 114 , 115 ). In the context of attachment more specifically, the formation of a preference for a partner across species is also accompanied by rejection, often aggressively, of a novel mate ( 14 , 40 ). Thus, understanding the antisocial correlates of attachment neurobiology may be key to examining the etiology of prejudice, xenophobia, and intergroup violence.…”
Section: Attachment Behavior Influences Health Across the Lifespanmentioning
confidence: 99%
“…A wealth of data from other species suggests not only that there is a neural substrate for attachment and prosocial behavior, but that it also developed by evolutionary selection (19,39). Across species, social attachments have been defined by similar patterns of behavior, including mate (or pair) bonding, biparental care, and peer affiliation (36,40). Adult pair bonds are characterized by long-term, preferential mating between two individuals and the active rejection of novel potential mates (14,17,41).…”
Section: Integrating Social Attachment and Prosocial Behaviormentioning
confidence: 99%
“…Prairie voles also display similar levels of aggression in females and males. Males attack novel conspecifics at low levels, but upon pairbond formation, both sexes show selective aggression towards strangers (Getz et al, 1981;Lee and Beery, 2022;Tickerhoof et al, 2020;Wang et al, 1997;Young et al, 2011). Thus, a pair-bond encompasses both prosocial (towards the partner) and antisocial (towards novel conspecifics) behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain insight into prairie vole brain sexual differentiation, we assessed expression of Esr1, Esr2, and Ar within the SBN, using in situ hybridization (ISH) at postnatal day 14 (P14) in mice, prairie, and meadow voles. The inclusion of meadow voles permits comparisons within two Microtus species and provides a behavioral intermediate between polygamous mice and monogamous prairie voles: meadow voles show a partner preference for same-sex peers and engage in seasonal social group living (Anacker et al, 2016;Beery, 2019;Beery et al, 2014;Lee and Beery, 2022). We selected ISH to allow a consistent methodology across all three genes.…”
Section: Introductionmentioning
confidence: 99%